Formulation and Evaluation of Sustained Release Ondansetron Poloxamer Based Solid Suppositories - Zawar L R, Bhandari G S (Journal of Applied Pharmaceutical Science)
The present investigation studies the effect of water swellable polymer hydroxylpropylmethyl cellulose (HPMC K4M, Methocel) on in vitro release of ondansetron from suppositories. Suppositories were prepared by using mixture of Poloxamer 407 and Poloxamer 188 hydrophilic bases. Suppositories containing 16 mg of ondansetron were prepared by fusion method. Weight variation, content uniformity, breaking (hardness), disintegration time, melting point and liquefaction time of the formulations were determined. In vitro release test was carried out according to USP XXII basket method. In vitro release data demonstrates ondansetron release from suppositories up to 12hrs and follows the zero order kinetics from poloxamer mixture based suppositories.
Keywords: Ondansetron, Poloxamer 407, poloxamer 188, HPMC, sustain release.